The effects of nitrogen atmosphere pressure, constant and high-voltage pulse potentials of the substrate on the structure and properties of vacuum-arc ZrN coatings - Sobol’, O.V.; Andreev, A.A.; Stolbovoy, V.A.; Gorban’, V.F.; Pinchuk, N.V.; Meylekhov, A.A. (Вопросы атомной науки и техники, 2015)
ZrN-phase coatings with a cubic lattice (NaCl structure type) were produced by the method of vacuum-arc evaporation of a Zr cathode in nitrogen atmosphere at pressures PN between 0.02 and 0.64 Pa. The pressure increase at a bias potential of -150 V leads to formation of the growth texture [111] or to appearance of the bitextural state with the axes [111] and [311]. Additional pulsed-mode supply of high-voltage negative potential Uip = 800…2000 V, with pulse duration of 10 μs and frequency of 7 kHz, stimulates the emergence of texture [110]. At the substructure level, the Uip supply causes the microstrain relaxation and the crystallite size growth with increasing pressure. The observed changes are attributed to increased particle mobility and nitride formation activity under the action of Uip. The hardness increases with increasing pressure and reaches a value of 43 GPa. The Uip supply leads to a shift of the maximum hardness towards higher pressures. Методом вакуумно-дугового испарения Zr-катода в азотной атмосфере при давлении PN = 0,02…0,64 Па получены покрытия ZrN с кубической (структурный тип NaCl) кристаллической решеткой. Повышение давления при потенциале смещения -150 В приводит к образованию текстуры роста [111] или появлению битекстурного состояния с осями [111] и [311]. Дополнительная подача высоковольтного отрицательного потенциала Uпи = 800…2000 В в импульсном режиме с длительностью 10 мкс и частотой 7 кГц стимулирует появление текстуры [110]. На субструктурном уровне подача Uпи приводит к релаксации микродеформации и росту размеров кристаллитов при повышении давления азота. Наблюдаемые изменения связываются с повышением подвижности частиц и активности нитридообразования в условиях действия Uпи. Твердость возрастает с увеличением давления и достигает значения 43 ГПа. Подача Uпи приводит к смещению максимальной твердости в сторону больших давлений. Методом вакуумно-дугового випаровування Zr катода в азотній робочій атмосфері при тиску PN = 0,02…0,64 Па отримані покриття ZrN з кубічною (структурний тип NaCl) кристалічною решіткою. Підвищення тиску в умовах дії негативного потенціалу зсуву -150 В призводить до утворення текстури росту [111] або появи бітекстурного стану з осями [111] і [311]. Додаткова подача високовольтного негативного потенціалу Uпі = 800...2000 В у імпульсному режимі з тривалістю 10 мкс і частотою 7 кГц стимулює появу текстури [110]. На субструктурному рівні високовольтний імпульсний вплив призводить до релаксації мікродеформації і зростанню розмірів кристалітів при підвищенні тиску азоту. Спостережувані зміни пов'язуються з підвищенням рухливості частинок і активності нітридоутворення в умовах дії Uпі. Твердість зростає із збільшенням тиску і досягає значення 43 ГПа. Подача Uпі призводить до зсуву максимальної твердості в бік великих тисків.